PEMETAAN IRIGASI DAN PRODUKTIFITAS TANAH SAWAH DI DESA LAWELE KECAMATAN LASALIMU KABUPATEN BUTON - Safiun, Safiun; Syaf, Hasbullah; Yusuf, Dewi Nurhayati; Darwis, Darwis; Pasolon, Yulius B.; Rustam, La Ode (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study aims to determine the fertility status of irrigated paddy fields in various types of irrigation networks, as well as its relationship to crop productivity in the rice fields of Lawele Village, Lasalimu District, Buton Regency, Southeast Sulawesi Province. This research was conducted from June to October 2022. The method used is a descriptive method through field surveys and analysis in the laboratory. Sampling was carried out in a moving sequence based on the type of irrigation channel, and soil samples were taken at a depth of (0-20) cm. Soil chemical parameters analyzed were C-organic, total P2O5, total K2O, KTK, and KB. Determination of fertility status is guided by the PPT Soil Research Center, Bogor (1995). Problems that occur in irrigation in Lawele Village, Lasalimu District, are uneven distribution and poor physical condition of irrigation networks, as well as low soil fertility and crop productivity for various types of irrigation. The results showed that the fertility status of irrigated paddy fields on each land irrigated with various types of irrigation networks was very low. Fertility parameters that become obstacles in this soil fertility status are total K, total P, and some soil organic C which causes low land productivity in irrigated rice fields in Lawele Village. This is due to the leaching of soil cations as well as the lack of application of organic fertilizers and NPK by irrigation. Keywords: Fertility, Productivity, Rice Field